Modelling of the antecedents of staff satisfaction on turnover intention in a Malaysian Public University - Mohamad Hazeem, Mohmad Sidik (2017)
Staff is regarded as asset that could take the organisation to greater productivity and performance. Studies on staff satisfaction are of great importance and should be taken seriously as issues of dissatisfaction would raise rippling effects at the workplace and cause turnover in any organisation including higher educational institutions (HEIs). Therefore, the main purpose of this study is to develop a hypothesised model on the impact of predictors for staff satisfaction on turnover intention and to empirically examine the relationships that are hypothesised in the research model that was developed based on literature reviews and related underpinning theories. The study employed a quantitative method using questionnaire that was adopted and adapted from previous study. Structural Equation Modelling (SEM) through Partial Least Squares (PLS) estimation are used for the analysis. A sample of 1042 secondary data from UMP staff was involved in the study that was clusterly sampled for 2015 from 4 consecutive years i.e. 2012, 2013, 2014 and 2015, conveniently. The results revealed that leadership, staff involvement, workload, self-development, working environment and communication are related to the overall satisfaction which has consequential impact on the turnover intention. In conclusion, the predictors under study could determine the staff satisfaction and this leads to their intention to stay or leave the organisation. The findings found a significant relationship between each of the linkages among variables studied on staff satisfaction and turnover intention at p < 0.05. This finding could be used for university management to look into possible rooms for improvement in ensuring that staff satisfaction within the university system as this would eventually ensure sustainability and survivality of university.